Analysis of the Relationship between Anxiety Level and Smash Accuracy of Badminton Athletes - Arimbi; Andi Ainun Zulkiah Surur; Poppy Elisano Arfanda; Wahyana Mujari Wahid; HarvinaMukrim; Chaerul Fadly Mochtar Luthfi (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to analyse the relationship between anxiety level and smash accuracy in badminton athletes. Anxiety is one of the psychological factors that can affect athlete performance, especially in sports that require concentration and accuracy such as badminton. This study uses a quantitative approach with a correlational design. Data were collected through anxiety questionnaire and smash accuracy measurement through validated skill test. The results of the analysis show that there is a significant relationship between anxiety levels and athletes' smash accuracy. The higher the level of anxiety experienced by athletes, the lower the smash accuracy displayed, and vice versa. This finding indicates the importance of managing psychological aspects in athlete training to improve technical performance on the field.